2, 2′, 4, 4′, 5‐Pentabromodiphenyl ether induces lipid accumulation throughout differentiation in 3T3‐L1 and human preadipocytes in vitro. Issue 6 (4th March 2020) - Armstrong, Laura E.; Akinbo, Stephen; Slitt, Angela L.
Abstract: Flame retardants, specifically polybrominated diphenyl ethers (PBDEs), are chemical compounds widely used for industrial purposes and household materials. NHANES data indicate that nearly all Americans have trace amounts of PBDEs in serum, with even higher levels associated with occupational exposure. PBDEs are known to bioaccumulate in the environment due to their lipophilicity and stability, and more importantly, they have been detected in human adipose tissue. The present study examined whether the PBDE congener, BDE‐99 (2, 2′, 4, 4′, 5‐pentabromodiphenyl ether; 0.2‐20 μM), enhances the adipogenesis of mouse and human preadipocyte cell models in vitro via induced lipid accumulation. 3T3‐L1 mouse preadipocytes and human visceral preadipocytes demonstrated enhanced hormone‐induced lipid accumulation upon BDE‐99 treatment. In addition, BDE‐99 (20 μM) induced preadipocyte differentiation and lipid development in nondifferentiated human preadipocytes. BDE‐99, the second most abundant congener in human adipose tissue, increased total lipids in differentiating adipocytes and therefore showed a potential role in the regulation of adipogenesis. This warrants more research to further understand the impact of lipophilic persistent pollutants on adipose tissue homeostasis.